HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN UPAYA INTERVENSI DINI GANGGUAN PENDENGARAN DI SURAKARTA - Susanti, Nadya (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
A hearing impairment is the inability to clearly hear sounds. The hearing system could have been damaged by disease, poor development, or both. The development of typical speech and language is dependent upon hearing. The speech of people in the child’s family and environment helps them learn to talk. Speech and hearing are more crucial for a developing child than they are for an adult since they are the tools used for learning, playing, and establishing social skills. A child who has hearing loss and is not identified or intervened at an early age will experience a number of losses. Delays in detection and intervention can cause social behavioral problems, academic challenges, and delays in speech and/or language development. A parent or mother should also guarantee that the child receives an early diagnosis, early cochlear implant surgery if necessary, early hearing aid fitting, and early start to special education programs that can help the child’s hearing and understanding and ensure better development early on. This study, which was carried out in the city of Surakarta using a cross sectional study design. A sample of 30 people was selected using a purposive sampling. Data collection was performed using a questionnaire and analyzed by Chi Square. The results of the chi-square test obtained a value of p<0.05 with p = 0.032, so that it is possible to draw the conclusion that there is a significant connection between early intervention and the mother’s knowledge. The greater the mother’s knowledge, the better her efforts to provide early intervention in children with hearing loss.